2018
DOI: 10.1080/2162402x.2017.1404214
|View full text |Cite
|
Sign up to set email alerts
|

OX40 expression in hepatocellular carcinoma is associated with a distinct immune microenvironment, specific mutation signature, and poor prognosis

Abstract: Immunotherapy's effect against hepatocellular carcinoma (HCC) is hampered by immunosuppressive mechanisms in the tumor microenvironment. We assessed the clinicopathologic and biologic relevance of OX40, a costimulatory molecular expressed by regulatory T cells (Tregs), in HCC. We analyzed the immunohistochemistry data of 316 patients treated at West China Hospital (WCH) and the RNA sequencing data of 370 patients in The Cancer Genome Atlas (TCGA) to determine the clinicopathologic significance of OX40 in HCC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 48 publications
4
67
0
Order By: Relevance
“…Similar to our result, high expression of LAG-3 predicted poor survival in head and neck squamous cell carcinoma [41], melanoma [37], soft tissue sarcomas [42] and nonsmall cell lung cancer(NSCLC) [40]. On the contrary, other studies in esophageal squamous cell carcinoma [43], breast cancers [39] and NSCLC [44]show the opposite results, and only one study in HCC has showed no prognostic significance [45]. Differences in patient cohorts, disease types, and selection of cutoffs can contribute to the discrepancy.…”
Section: Discussionsupporting
confidence: 84%
“…Similar to our result, high expression of LAG-3 predicted poor survival in head and neck squamous cell carcinoma [41], melanoma [37], soft tissue sarcomas [42] and nonsmall cell lung cancer(NSCLC) [40]. On the contrary, other studies in esophageal squamous cell carcinoma [43], breast cancers [39] and NSCLC [44]show the opposite results, and only one study in HCC has showed no prognostic significance [45]. Differences in patient cohorts, disease types, and selection of cutoffs can contribute to the discrepancy.…”
Section: Discussionsupporting
confidence: 84%
“…Similar to our result, high expression of LAG-3 predicted poor survival in head and neck squamous cell carcinoma [41], melanoma [37], soft tissue sarcomas [42] and non-small cell lung cancer (NSCLC) [40]. On the contrary, other studies in esophageal squamous cell carcinoma [43], breast cancers [39] and NSCLC [44] show the opposite results, and only one study in HCC has showed no prognostic signi cance [45]. Differences in patient cohorts, disease types, and selection of cutoffs can contribute to the discrepancy.…”
Section: Discussionsupporting
confidence: 84%
“…Several studies on OX40 and OX40L in cancer patients have been conducted. Xie et al [23] found that high OX40 expression in TIL hepatocellular carcinoma correlates with poor survival. Rothfelder et al [24] reported that OX40 expression was related to shorter survival in myeloid leukemia.…”
Section: Discussionmentioning
confidence: 99%